Eglises et santé dans le Tiers Monde :hier et aujourd'hui = Churches and health care in the Third World : past and present - Pirotte, Jean.; Derroitte, Henri. (Studies in Christian Mission, 1991)
The fifteen papers presented here examine three centuries of close, if sometimes ambiguous, links between Christian mission and medicine. The authors, who include theologians, historians, sociologists, physicians and representatives of major international health-care organisations, address themselves to such questions as: How is one to assess the results of past missionary health-care effort? How are modern-day Christian organisations to cope with the burden of institutions set up in the past? What links should the Churches maintain with official medical organisations? What position should the Churches take on the 'faith volume healing' debate begun by certain religious groups? And how is one to lay the groundwork of a theology of health and healing? The complexity of the issues outlined here can - alas - provide no easy answers. Quinze auteurs, compris théologiens, historiens, sociologues, médecins et responsables d'organisations sanitaires, ont centré leurs réflections sur le rôle des Églises chrétiennes dans le domaine de la santé, hier dans les pays de mission, aujourd'hui dans ces mêmes régions où se mûrit une véritable inculturation du christianisme. Dans cet ouvrage ils abordent plusieurs questions fondamentales: comment évaluer les résultats et lacunes de l'action sanitaire des missions dans le passé? Les communautées chrétiennes actuelles doivent-elles porter le poids d'institutions mises en place hier? Quels rapports les Églises doivent-elles entretenir avec les organisations médicales officielles? Comment les Églises se situent-elles dans la dialectique 'foi-guérison' développée par certains groupes religieux? Plus profondément, comment poser les jalons d'une théologie de la santé et de la guérison? Trouver les reponses sur ces questions complexes c'est une tache très délicate.